"Nepalese Women Immigrants in Portugal" - Pereira, A. (Workshop Gender and Migration IGOT/IMISCOE, 2016)
in Artigos e Comunicações Para Workshop Gender and Migration - 2016, IGOT/IMISCOE, Universidade de Lisboa.